2017
DOI: 10.29050/harranziraat.321185
|View full text |Cite
|
Sign up to set email alerts
|

İçme Sütü Üretiminde ESL (Extended Shelf Life) Teknolojisinin Kullanımı

Abstract: ÖzGünümüzde içme sütü üretim teknolojisinde, en çok bilinen ve uygulanan ısıl işlemler pastörizasyon ve UHT teknolojisidir. Pastörizasyonla kısa ömürlü ancak taze bir ürün elde edilirken; UHT ile uzun ömürlü ancak duyusal olarak beğeni düzeyi daha düşük bir ürün elde edilmektedir. Bu bağlamda ESL teknolojisi, pastörize süte göre daha uzun ömürlü ve duyusal olarak tüketiciye daha cazip bir ürün sunmak amacıyla geliştirilmiş yeni bir yöntemdir. Bu yöntem; mikrofiltrasyon, baktofügasyon, vurgulu elektriksel alan,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…In previous studies, Al concentration was reported to vary between 2.518 and 9.130 mg/L in milk (Akın et al, 2003;Algan et al, 2003;Maurício et al, 1988;Özrenk, 2002). In our study, Al Likewise, at high temperatures, calcium and phosphate turn into an insoluble form (De La Fuente et al, 1999;Ünver & Şerafettin, 2017). In our study, calcium and phosphate concentrations of milk among applications were not found to be different.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In previous studies, Al concentration was reported to vary between 2.518 and 9.130 mg/L in milk (Akın et al, 2003;Algan et al, 2003;Maurício et al, 1988;Özrenk, 2002). In our study, Al Likewise, at high temperatures, calcium and phosphate turn into an insoluble form (De La Fuente et al, 1999;Ünver & Şerafettin, 2017). In our study, calcium and phosphate concentrations of milk among applications were not found to be different.…”
Section: Discussionsupporting
confidence: 58%
“…Likewise, at high temperatures, calcium and phosphate turn into an insoluble form (De La Fuente et al., 1999; Ünver & Şerafettin, 2017). In our study, calcium and phosphate concentrations of milk among applications were not found to be different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These microorganisms may cause undesirable changes in the taste, smell, color, sensory and structural properties of food (Lucera et al, 2012;Ünver and Çelik, 2017;Yaralı, 2019). Various preservation methods such as fermentation, drying, heat treatment, organic acid application, UV ionizing radiation, non-thermal applications such as high hydrostatic pressure are used in the food industry to prevent the development of spoilage and pathogenic microorganisms in foods (Davidson and Taylor, 2007;Farkas, 2007;Ünver and Çelik, 2017;Belibağlı and Ersan, 2018). In recent years, there has been a significant increase in the preservation of food with natural additives due to consumer concern about synthetic chemicals used in foods (Lucera et al, 2012).…”
Section: Introductionmentioning
confidence: 99%